BRUXISMO INFANTIL: INVESTIGAÇÃO SOBRE CONHECIMENTO DE EDUCADORES E CRIAÇÃO DE PLATAFORMA DIGITAL - Sanchotene, Manoella Corcini (2024)
Bruxism is characterized as a repetitive, rhythmic and involuntary activity of the chewing muscles, which is manifested by clenching and/or grinding of the teeth. When it comes to childhood bruxism, an increase in its prevalence has been identified in recent years. Currently, children spend most of their time in a school environment, with educators being responsible for the child during this period. In this context, this environment has great relevance in enabling the initial perception of the habit, above all, to alert parents about it. However, it is necessary for pedagogical teams to be informed and equipped to do so. Objective of scientific research: Verify and understand knowledge about childhood bruxism on the part of educators of preschool children in a municipality in the interior of the state of Rio Grande do Sul. Objective of the technical product: Develop an interactive digital platform, about child bruxism, aimed at educators and parents. Scientific research methodology: This is a qualitative study that was carried out with 19 educators from three municipal early childhood schools in the city of Alegrete, Rio Grande do Sul. The sample was carried out by convenience and the number of interviews was determined by saturation . The interviews were carried out by a single, previously trained researcher. First, the socioeconomic information of the participants was collected. These variables were used to describe the characteristics of the study sample. A pilot study was carried out. All questions in the semi-structured interview were conducted with an audio recorder. The transcribed speeches were analyzed according to the thematic content analysis proposed by Braun and Clark (2006). Technical product methodology: Based on data collection from educators and scientific evidence, an interactive digital platform was created containing videos and information about childhood bruxism. The platform will be made available for use by early childhood education educators, and can also be extended to parents/guardians of children and be used in dental offices, with wide dissemination. The technology created according to the Qualis Coordination for the Improvement of Higher Education Personnel (CAPES) stratum has T1=100 points. Monitoring and control of the use of this product will be carried out jointly between the researcher and educators. This monitoring will be verified through meetings. Results: The data collected by the research instrument demonstrated that educators have little knowledge on the topic, making it possible to support discussions in order to develop an interactive digital platform that contributes to guiding educators about information about childhood bruxism. Given this, it was possible to develop the most appropriate tools so that knowledge is transmitted in a simple, objective and dynamic way. Final Considerations: It is necessary that this topic is prioritized within the child care line and the importance of developing a platform that effectively contributes to improving the knowledge of educators and parents is reinforced, making them improve their understanding of bruxism children, as well as significantly assisting in the detection of the habit, contributing to and enabling early diagnosis, and, through professional monitoring, providing the affected child with greater comfort and a better quality of life. Product and its applicability: The technology created was an informative digital platform that will support and contribute to the early diagnosis of childhood bruxism, enabling more attentive and comprehensive care for the affected child. A high impact is expected in the medium and long term, from the use of this platform, which will equip educators so that they can assist with issues related to guidance on the topic of child bruxism, with broad scope, potential for replicability and innovation.